Are β-Lactones Involved in Carbon-Based Olefination Reactions? - Nowak, Jan; Tryniszewski, Michał; Barbasiewicz, Michał (Synlett, 2024)
Heteroatom-based olefinating reagents (e.g., organic phosphonates, sulfonates, etc.) are used to transform carbonyl compounds into alkenes, and their mechanism of action involves aldol-type addition, cyclization, and fragmentation of four-membered ring intermediates. We have developed an analogous process using ethyl 1,1,1,3,3,3-hexafluoroisopropyl methylmalonate, which converts electrophilic aryl aldehydes into α-methylcinnamates in up to 70% yield. The reaction plausibly proceeds through the formation of β-lactone that spontaneously decarboxylates under the reaction conditions. The results shed light on the Knoevenagel–Doebner olefination, for which decarboxylative anti-fragmentation of aldol-type adducts is usually considered.
Keywords: olefination; carbonyl compounds; reaction mechanism; lactones; malonates; Knoevenagel–Doebner reaction